2023
DOI: 10.1001/jamanetworkopen.2023.3944
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Mother-Adolescent and Father-Adolescent Relationships and Young Adult Health

Abstract: ImportanceStudies linking the quality of parent-adolescent relationships with young adult health outcomes could inform investments to support these complex relationships.ObjectiveTo evaluate whether consistently measured, modifiable characteristics of parent-adolescent relationships are associated with young adult health across multiple domains.Design, Setting, and ParticipantsThis cohort study used data from waves I (1994-1995; ages 12-17 years) and IV (2008-2009; ages 24-32 years) of the US National Longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Family support is an important factor that mitigates negative health outcomes among LGBTQ+ adolescents . Family support is a broad concept, including emotional and instrumental support, affirmation, and positive social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Family support is an important factor that mitigates negative health outcomes among LGBTQ+ adolescents . Family support is a broad concept, including emotional and instrumental support, affirmation, and positive social interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the frequency of changes in religious identification and the established importance of the family context on religious changes, relatively little research has been done to examine the bidirectional relationships between religious changes and family relationships in accordance with the relational developmental systems framework. Further, a deeper understanding of how these religious shifts may impact the parent child-relationship is critical because positive parent-child relationships in adolescence and young adulthood are tied to reduced substance abuse and increased relational, physical, and mental health and well-being for children (Ford et al 2023) and an increased likelihood that children will provide support to their parents in later years (Lin and Wu 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Further, a deeper understanding of how these religious shifts may impact the parent child‐relationship is critical because positive parent‐child relationships in adolescence and young adulthood are tied to reduced substance abuse and increased relational, physical, and mental health and well‐being for children (Ford et al. 2023) and an increased likelihood that children will provide support to their parents in later years (Lin and Wu 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Parent-adolescent relationships play a crucial role in adolescent development and are associated with multiple physical and mental health outcomes in both the short and long term [ 8 , 9 ]. Previous research has also shown that adolescents with low-quality parent-adolescent relationships tend to experience more psychosomatic complaints [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%